2017
DOI: 10.1002/cncr.30546
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pre‐transplant depression on outcomes of allogeneic and autologous hematopoietic stem cell transplantation

Abstract: Background To evaluate the impact of depression prior to autologous and allogeneic HCT on clinical outcomes post-transplant. Methods We analyzed data from the Center for International Blood and Marrow Transplant Research to compare outcomes after autologous (n=3786) or allogeneic (n=7433) HCT for adult patients with hematologic malignancies with an existing diagnosis of pre-HCT depression requiring treatment vs. those without pre-HCT depression. Using Cox regression models, we compared OS between patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
50
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 35 publications
2
50
0
1
Order By: Relevance
“…The present null findings are somewhat unexpected given prior evidence from other HCT populations suggesting an association between pre-transplant SES and PRO variables and clinical outcomes [4,5,9,11,12,22,29,35,45]. Recently, Wood et al [29] identified that the pre-transplant PCS scale independently predicted overall mortality in the same cohort of autologous and allogeneic HCT recipients used in the present study.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…The present null findings are somewhat unexpected given prior evidence from other HCT populations suggesting an association between pre-transplant SES and PRO variables and clinical outcomes [4,5,9,11,12,22,29,35,45]. Recently, Wood et al [29] identified that the pre-transplant PCS scale independently predicted overall mortality in the same cohort of autologous and allogeneic HCT recipients used in the present study.…”
Section: Discussionsupporting
confidence: 46%
“…It is possible that the significant physical and immunological perturbation inherent in the HCT process and the underlying heterogeneity of the study population obfuscate any potential relationship between emotional status and immunologic determinants that could impact outcomes. In particular, the powerful immunosuppressive agents used to prevent and treat GVHD in allogeneic recipients may overshadow any influence of SES and PRO factors on immune function, although there is prior evidence to suggest otherwise [4,45]. Given the observation of this relationship in smaller cohorts, it seems less plausible that true associations would not be evident in our significantly larger cohort, unless there was not sufficient adjustment for other transplant-, disease-, and patient-related factors in prior studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also showed that a history of psychiatric disease was relatively common and associated with worse OS and a higher incidence of TRM in multivariable analysis, while other psychosocial issues were found to be prevalent in AYA patients, but did not correlate with increased mortality. While often overlooked by physicians, prior studies have revealed higher rates of acute GVHD and lower OS in patients with a psychiatric history . It is not clear how mental illness impacts survival outcomes, but it likely is associated with the high rates of noncompliance and risky behaviors seen in patients with psychiatric disorders .…”
Section: Discussionmentioning
confidence: 58%
“…While often overlooked by physicians, 38 prior studies have revealed higher rates of acute GVHD and lower OS in patients with a psychiatric history. [39][40][41] It is not clear how mental illness impacts survival outcomes, but it likely is associated with the high rates of noncompliance and risky behaviors seen in patients with psychiatric disorders. 42 Thus, while a significant association was not seen with psychosocial problems in our study, psychiatric and psychosocial issues are certainly related and may impact outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Also, patients undergoing autologous HSCT with pre-transplantation depression had fewer days alive out of hospital. 26 In another study, it was shown that patients suffering from depression according to HADS questionnaire, had a relative risk factor for their overall survival following HSCT. In other words, depressed patients (with HADS score =10) were more than two-and-a-half times more likely than non-depressed patients (with HADS score = 0) to die after HSCT.…”
Section: Discussionmentioning
confidence: 98%